Analisis Pola dan Dampak Serangan Cryptojacking dengan Menggunakan Metode Analisis Dinamis dan Analisis Statis - Mesakh Herdian Pamungkas; Dian Widiyanto Chandra (JURIKOM (Jurnal Riset Komputer), 2022)
In the current era of globalization, people's daily activities are highly dependent on technology. The development of this technology is certainly utilized by many different parties. In addition to taking advantage of the positive side, there are also parts that take advantage of the negative side. In this case it is like developing criminal software or what is commonly called cybercrime. One form of this crime is cryptojacking. Cryptojacking is the dark side of cryptocurrency mining and poses a threat to website visitors or end-users. This research was carried out with a 6-step method which resulted in the result that based on static and dynamic malware analysis, the installation of Crackonosh itself runs by replacing important files on the Windows system and abusing Windows Safe Mode to damage the order and defense of the Windows system